Here - Hither - Hence and Related Categories A Cross-linguistic Study - Nintemann, Julia (Studia typologica ;, 2020)
As a follow-up study to the global comparison of spatial interrogatives (Studia Typologica 20), the present book examines the spatial declarative counterparts which are provided by the expression class of spatial deictic adverbs. In a functionally motivated typological approach, equivalents of Early Modern English here - hither - hence and there - thither - thence are identified across a sample of 250 languages from all macro-areas. These are also quantitatively assessed to extrapolate areal and global trends of coding patterns. The formal relationships between spatial interrogative and spatial declarative paradigms are analyzed with a focus on the syncretism of categories and of individual cells. Qualitative discussions of patterns precede in-depth treatments of problematic cases and other relevant issues related to the research topic.The quantitative results strongly point to areal linguistic trends concerning the distribution of distinct and non-distinct coding of the three spatial relations Place, Goal, and Source. Additional aspects such as quantitative evaluations of constructional complexity are addressed subsequently.